Molecular mechanism of the influence of related genes expression in synovium tissue around shoulder joint of secondary frozen shoulder model rats on angiogenesis: Genetic of angiogenesis in secondary frozen shoulder - Xu, Jie; Ren, Dong; Liu, Fei; Liu, Shuren; Wang, Pengcheng (Cellular and Molecular Biology, 2024)
The study aimed to explore the pathogenesis of secondary frozen shoulder and its influence on synovium tissue and angiogenesis by constructing a rat secondary frozen shoulder model along with transforming growth factor. 40 healthy male rats aged 8 weeks were divided into Sham group (n=10, no modeling treatment), Control group (n=10, modeling treatment), Low group (n=10, modeling treatment, and 10 mL/d transforming growth factor), and High group (n=10, modeling treatment, and 20 mL/d transforming growth factor). Hematoxylin and Eosin (HE) method was used for histological detection, and Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and immunohistochemical staining method were adopted to detect the expression of Matrix metalloproteinase-14 (MMP-14), mitogen-activated protein kinase (p38MAPK), and Vascular endothelial growth factor (VEGF). Compared with Sham group, the range of abduction and external rotation of rat glenohumeral joint in Control group, Low group, and High group was significantly reduced, and High group had the smallest range. Compared with the Sham group, the synovium in the Control group, the Low group, and the High group had obvious hyperplasia, and the blood vessels were significantly increased. Immunohistochemical staining and RT-PCR results showed that compared with Sham group, MMP-14, p38 MAPK, and VEGF in Control group, Low group, and High group all increased significantly, among which High group increased most. The secondary frozen shoulder is mainly manifested as synovial hyperplasia and increased blood vessels, which are related to the induction of MMP-14, p38 MAPK, and VEGF by transforming growth factor, which reveals the pathogenesis of secondary frozen shoulder to a certain extent, and lays a foundation for subsequent clinical treatment of secondary frozen shoulder.